Literature and architecture in early modern England - Myers, Anne M. (Johns Hopkins University Press, 2013)
Buildings tell stories. Castles, country homes, churches, and monasteries are “documents” of the people who built them, owned them, lived and died in them, inherited and saved or destroyed them, and recorded their histories. This book examines the relationship between sixteenth- and seventeenth-century architectural and literary works. By becoming more sensitive to the narrative functions of architecture, the author argues, we begin to understand how a range of writers viewed and made use of the built environment that surrounded the production of early modern texts in England.